Sensorimotor modulation by botulinum toxin A in post-stroke arm spasticity: Passive hand movement - Veverka, Tomáš; Hluštík, Petr; Hok, Pavel; Otruba, Pavel; Zapletalová, Jana; Tüdös, Zbyněk; Krobot, Alois; Kaňovský, Petr (Journal of the neurological sciences, 2016)
INTRODUCTION: In post-stroke spasticity, functional imaging may uncover modulation in the central sensorimotor networks associated with botulinum toxin type A (BoNT) therapy. Investigations were performed to localize brain activation changes in stroke patients treated with BoNT for upper limb spasticity using functional magnetic resonance imaging (fMRI). METHODS: Seven ischemic stroke patients (4 females; mean age 58.86) with severe hand paralysis and notable spasticity were studied. Spasticity was scored according to the modified Ashworth scale (MAS). fMRI examination was performed 3 times: before (W0) and 4 (W4) and 11weeks (W11) after BoNT. The whole-brain fMRI data were acquired during paced repetitive passive movements of the plegic hand (flexion/extension at the wrist) alternating with rest. Voxel-by-voxel statistical analysis using the General Linear Model (GLM) implemented in FSL (v6.00)/FEAT yielded group session-wise statistical maps and paired between-session contrasts, thresholded at the corrected cluster-wise significance level of p<0.05. RESULTS: As expected, BoNT transiently lowered MAS scores at W4. Across all the sessions, fMRI activation of the ipsilesional sensorimotor cortex (M1, S1, and SMA) dominated. At W4, additional clusters transiently emerged bilaterally in the cerebellum, in the contralesional sensorimotor cortex, and in the contralesional occipital cortex. Paired contrasts demonstrated significant differences W4>W0 (bilateral cerebellum and contralesional occipital cortex) and W4>W11 (ipsilesional cerebellum and SMA). The remaining paired contrast (W0>W11) showed activation decreases mainly in the ipsilesional sensorimotor cortex (M1, S1, and SMA). CONCLUSIONS: The present study confirms the feasibility of using passive hand movements to map the cerebral sensorimotor networks in patients with post-stroke arm spasticity and demonstrates that BoNT-induced spasticity relief is associated with changes in task-induced central sensorimotor activation, likely mediated by an altered afferent drive from the spasticity-affected muscles.
Keywords: Magnetic Resonance Imaging; botulotoxiny typu A; neparametrická statistika; magnetická rezonanční tomografie; Humans; lidé středního věku; Stroke; kvadruplegie; neurotoxiny; Female; Aged; Neuronal plasticity; Botulinum Toxins, Type A; senioři; lidé; Neurotoxins; mozková kůra; Neurologic Examination; počítačové zpracování obrazu; Electromyography; Image Processing, Computer-Assisted; Cerebral Cortex; neurologické vyšetření; cévní mozková příhoda; Oxygen; Quadriplegia; kyslík; Follow-Up Studies; ženské pohlaví; Kinesthesis; Functional magnetic resonance imaging; Male; Middle Aged; Spasticity; Statistics, Nonparametric; kinestezie; Hand weakness; mužské pohlaví; elektromyografie; Botulinum toxin; následné studie